Publications: Agriculture and nutrition in Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications share knowledge and data that can contribute to improving food security and nutrition in Africa.